Numerical analysis of the effects of the bending stiffness of the cable and the mass of structural members on free vibrations of suspension bridges - Grigorjeva, Tatjana (Journal of Civil Engineering and Management, 2015)
The article determines natural frequencies of vibration and the corresponding mode shapes of a suspension bridge with the varying bending stiffness of cables and examines variations that occur in these characteristics with respect to parametric changes in the bridge. A single span suspension steel footbridge with flexible cables has been selected as an initial model used for studying the dynamic characteristics of a suspension system. With the help of the finite elements (FE) method, parameter studies of the bridge model are presented in which vibration characteristics are studied as a function of structural and material parameters such as the flexural stiffness of the cable and the mass density of structural components. It has been generally found that the bending stiffness of the main cable contributes to a considerable effect on natural frequencies for this type of the suspension system. A simplified expression of predicting natural bending frequencies of the suspension bridge taking into account the bending stiffness of the cable has been developed for the application as the first step in the design process.